2015
DOI: 10.1002/jcp.24851
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epigenetic Mechanisms in Notch Signaling During Development

Abstract: The Notch pathway is a highly conserved cell-cell communication pathway in metazoan involved in numerous processes during embryogenesis, development, and adult organisms. Ligand-receptor interaction of Notch components on adjacent cells facilitates controlled sequential proteolytic cleavage resulting in the nuclear translocation of the intracellular domain of Notch (NICD). There it binds to the Notch effector protein RBP-J, displaces a corepressor complex and enables the induction of target genes by recruitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 83 publications
(166 reference statements)
0
61
0
1
Order By: Relevance
“…However, in the context of glomerular diseases, including FSGS and diabetic nephropathy, it can become reactivated, promoting podocyte dedifferentiation and accelerating glomerular damage (24,25,29). During development, chromatin remodeling provides an important means by which a cell can set, coordinate, and integrate Notch-dependent processes (41). The findings of the present study indicate that chromatin remodeling events are similarly involved in the reactivation of developmental processes during the occurrence of glomerular disease.…”
Section: Discussionmentioning
confidence: 60%
“…However, in the context of glomerular diseases, including FSGS and diabetic nephropathy, it can become reactivated, promoting podocyte dedifferentiation and accelerating glomerular damage (24,25,29). During development, chromatin remodeling provides an important means by which a cell can set, coordinate, and integrate Notch-dependent processes (41). The findings of the present study indicate that chromatin remodeling events are similarly involved in the reactivation of developmental processes during the occurrence of glomerular disease.…”
Section: Discussionmentioning
confidence: 60%
“…Notch receptors mediate an evolutionarily conserved intracellular signaling process that regulates cell fate (Schwanbeck, 2015). Many studies have demonstrated the role of Notch signaling during neural development including neurogenesis, gliogenesis, neuronal morphology, synaptic plasticity, learning and memory (Pierfelice et al, 2011).…”
Section: ) Notch Receptorsmentioning
confidence: 99%
“…Thus, Hh signaling could only promote the specification of KA" interneurons in LFP progenitors where Notch signaling was active. 69 How Notch signaling provides competence to respond to Hh remains unknown, but Notch signaling is known to alter chromatin state, 70,71 and it a likely mechanism for altering progenitor competence in this system.…”
Section: Epigenetic Silencing Of Notch Target Genes Restricts Inp Commentioning
confidence: 99%